A beteg kapcsolattartási jogáról - Petkó, Mihály (Debreceni Jogi Műhely, 2014)
Man is a social animal, it is important for colleagues to meet, create a relationship with them, to communicate, ideas, exchanging information. Human relationships are determined by the identity of a specific person, place in society, so it should be a fundamental right for all people in contact with the law. However, in certain life situations exercising these rights is necessarily limited, undermined, need frameworks. One of those situations in life with participation in health care in which the patient has to adapt in health care provider operating schedule, however, the Trustee is required to ensure the exercise of the right contacts. The most prominent of patients’ rights to human dignity, which is inferred from a mother right, from which a number of other important rights. One of these is the right to self-determination, which guarantees freedom of action of the human as an individual incapacity depending autonomous. For patient care recipients should be subject to the fundamental distinction that whether it is inpatient or outpatient care. In the latter case, it also suffers from significant limitations on the patient’s right to self-determination , including personal freedom, opportunities for contact with other people. The right to self-determination in a specific part of the realization of rights is thus involved in the regulation of the contact, as during inpatient care plays an important role. In today’s modern society, the means of communication, networks of past explosive development, get more involved in the exercise of the right to life, human relations than before, with the elimination of the technical obstacles the spatial and temporal obstacles easily can be prevented. Life situation of the theme chosen exercise of the right of communication is of particular importance, because the patient’s recovery depends not only on only physical but also mental condition, recovery can define what social relations, quality, intensity. The correspondence law of the health care law more the privileges include such other persons entitled to take the patient’s inpatient sanitation place either in writing or orally to maintain contact, to receive visitors, the people he set out to exclude the visit , prohibit the fact of his treatment or the other information related to medical treatment reveals other. The context of the law of correspondence can be said that relatively little addressed by legislators and by expanding the scope of the practice of law in the content, but would consider appropriate where more attention is added. It would be good detailed arrangements for the exercise of creating the right framework for the so - to clarify the scope of everyday objects, to establish rules for their use of health services that are appropriate for the task to allow the exercise of these rights - the first line telecommunications.